Bali’s Legong Pancer Langit Dance as Cultural Diplomacy and National Identity Construction: A Case Study of the Jeddah Festival - Kasmahidayat , Yuliawan; Yulianti, Elyana; Marbun, Saortua (Universitas Udayana, 2025)
This study examines the role of the Legong Pancer Langit Dance, a Balinese Hindu tradition rooted in Tri Hita Karana (harmony with God, humans, and nature), as a vehicle for cultural diplomacy and national character strengthening. Focusing on its 2023 performance at the Jeddah Cultural Festival, the research uses qualitative methods including interviews, observations, and document analysis. The movements like mutering jagat (rotational steps symbolizing unity) and ngelayak (back-bridge posture reflecting environmental stewardship) resonated with Islamic values such as tawazun (balance) and habluminnallah (human-God harmony). Adaptations like modest costumes and viral campaigns (#LegongEyeChallenge), enabled the dance to navigate cultural sensitivities while preserving authenticity. The study highlights the dance facilitated intercultural dialogue, reinforcing Pancasila values, and projecting national identity. Policy recommendations incorporating traditional arts into diplomatic education and leveraging augmented reality (AR) for heritage preservation. Ultimately, the Legong Pancer Langit exemplifies how intangible heritage can strengthen cultural diplomacy in globalized contexts.